Lipid safety of tenofovir alafenamide during 96-week treatment in treatment-naive chronic hepatitis B patients - Zhao, Wenjuan; Liu, Yi; Zhang, Mengdi; Cui, Zixin; Qu, Zhan; Li, Yiyang; Wan, Meijuan; Wang, Wen; Chen, Yunru; Shi, Lei; Li, Jianzhou; Ye, Feng (Frontiers in Medicine, 2024)
Background This study was aimed at investigating the dynamics of lipids and the effect of TAF on the lipid profile of patients including fatty liver disease in CHB patients. Methods The data of TC, LDL-c, HDL-c, TG, and TC/HDL ratio were collected at baseline, 24 weeks, 48 weeks, 72 weeks, and 96 weeks. CHB patients with fatty liver at baseline were further analyzed in a subgroup. Results A total of 137 CHB patients treated with TAF were enrolled in this study. During 96 weeks of TAF treatment, there was no significant change in TC, LDL-c, HDL-c, and TG level (P > 0.05). The TC/HDL-c ratio was increased with no significant change (+0.24, P > 0.05). In CHB patients with fatty liver (n = 48), TC, LDL-c, and TC/HDL-c ratio increased gradually during TAF treatment, TG levels increased to 146.63 mg/dL at 48 weeks (P = 0.057) and then decreased, but there was still no significant change compared with the baseline level by 96 weeks (P > 0.05). Conclusion TAF treatment had a low effect on the lipid profile of CHB patients over the course of 96 weeks, and it was safe even in patients with fatty liver. Clinical trial registration [https://www.chictr.org.cn/showproj.html?proj=65123], identifier [ChiCTR2000041005].